Knowledge and practice of health workers about control and prevention of multidrug-resistant tuberculosis in referral hospitals, Ethiopia: a cross-sectional study. Issue 2 (3rd February 2019) - Alene, Kefyalew Addis; Adane, Akilew Awoke; Yifiru, Sisay; Bitew, Bikes Destaw; Adane, Aynishet; Koye, Digsu Negese
Abstract : Objective: The aim of this study was to assess the knowledge and practice of health workers about multidrug-resistant tuberculosis (MDR-TB) prevention and control. Study design and settings: A cross-sectional study was conducted at Gondar University Referral Hospital and Felege Hiwot Referral Hospital. Participants: Randomly selected health workers (ie, medical doctor, nurse, health officer, pharmacy, medical laboratory and midwifery) were the study participants. Outcome measures: The main outcomes were knowledge and self-reported practice of health workers about MDR-TB. Results: A total of 377 health workers (with a response rate of 93.7%) participated in the study. The majority of respondents were nurses (52.5%, n=198) and medical doctors (15.6%, n=59). The mean knowledge score was seven out of 10; 149 (39.5%) of respondents scored seven or more which was considered as good knowledge. MDR-TB knowledge of health workers was significantly associated with having a postgraduate degree (adjusted odds ratio (AOR)=5.78; 95% CI 2.33 to 14.33), taking infection prevention training (AOR=1.79; 95% CI 1.00, to 3.17) and having a history of tuberculosis (TB) (AOR=1.85; 95% CI 1.12, to 3.03). The mean self-reported practice score was four out of seven; one-fifth (19.6%) of respondents scored four or more which was considered as good practice. Self-reported practice of health workers was significantly associated with working at internal medicine (AOR=4.64; 95% CI 1.99, to 10.81) and paediatrics (AOR=3.85; 95% CI 1.11, to 13.34) wards, being in the age groups of 26–30 years (AOR=2.70; 95% CI 1.27, to 5.76), and 30 years and above (AOR=4.42; 95% CI 1.77, to 11.00). Conclusions: This study found low knowledge and self-reported practice score among health workers. MDR-TB knowledge of health workers was significantly associated with educational status, infection prevention training and previous history of TB. This finding highlights the potential of providing MDR-TB training for health workers to increase their knowledge about MDR-TB.